Antioxidant activity in proteolytic enzyme digests of cashew (Anacardium occidentale L.) by-products - Nagaraja, K.V. (Journal of Plantation Crops, 2011)
Membrane filtration of proteolytic enzyme digests and NaOH extracts of solvent extracted flours of cashew by-products resulted in reduction in antioxidant activities. Gel filtration of proteolytic enzyme digests of solvent extracted flours of cashew processing by-products on Sephadex G 25 revealed the presence of two peaks one immediately after the void volume and another later during elution. Reducing power, arginine and proteins content reduced in enzyme digests and alkali extracts after gel filtration and membrane filtration.